THE HIGH-TEST CAST-IRON INDICATOR - G. E. Konovalov; A. R. Bajev; N. N. Gilj; N. I. Bestuzhev; P. S. Gurchenko (Литьë и металлургия, 2004)
It was concluded that the ultrasonic techniques are sensitive to the changes in the graphite morfology, thus they can also be used to predict the mechanical properties of cast iron. On the basis of the former an Indicator of ductile cast iron has been designed. The Indicator costruction and principles of its work are discussing.